2022
DOI: 10.1021/acsanm.2c02051
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Low-Energy Pt-Ion Implantation into Graphene for Single-Atom Catalysis

Abstract: Single-atom catalysts (SACs) represent the ultimate goal of nanocatalysis fields. However, complex synthesis processes and pyrolysis inactivation problems are the two main challenges that plague the development of SACs. In this work, we propose that the ultralow-energy ion-implantation (ULEII) method could be utilized to simply and efficiently synthesize stable SACs. Our simulation results of Pt-ion implantation into graphene indicate that the total doping efficiency, including direct displacement doping and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Furthermore, a similar method known as the ion implantation method is widely used to induce vacancies and defects in an efficient manner. 100 Using the ultralow-energy ion-implantation (ULEII) approach, the Hao group 7 investigated computationally in 2022 how platinum ions (Pt) could be injected onto graphene to induce defects. First-principles calculations and systematic molecular dynamics simulations of irradiation-induced vacancy defects showed that these defects efficiently supplied active sites to capture Pt single atoms onto the graphene surface.…”
Section: Methods Of Synthesis Of Single Atom Catalysts By the Defect ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a similar method known as the ion implantation method is widely used to induce vacancies and defects in an efficient manner. 100 Using the ultralow-energy ion-implantation (ULEII) approach, the Hao group 7 investigated computationally in 2022 how platinum ions (Pt) could be injected onto graphene to induce defects. First-principles calculations and systematic molecular dynamics simulations of irradiation-induced vacancy defects showed that these defects efficiently supplied active sites to capture Pt single atoms onto the graphene surface.…”
Section: Methods Of Synthesis Of Single Atom Catalysts By the Defect ...mentioning
confidence: 99%
“…5,6 In recent years, the scientic community has been witnessing an era of outstanding innovation in the domain of materials science and environmental catalysis, as exemplied by extraordinary single metal atom catalysts (SMACs). 7 SMACs have become valuable resources in the ght against climate change, with notable applications in nitrate (NO 3 − ) reduction to ammonia (NH 3 ) production, methane (CH 4 ) oxidation to various oxygenates, carbon dioxide (CO 2 ) reduction to valuable chemicals and fuels, including carbon monoxide (CO), formaldehyde (CH 2 O), acetic acid (CH 3 COOH), and n-propanol (n-C 3 H 7 OH), environmental monitoring, the oxygen reduction reaction (ORR) and the hydrogen evolution reaction (HER). [8][9][10] By virtue of their precise atomic-level structure and electronic properties, SMACs offer several advantages, encompassing high atomic utilization, quantum size effects, and promising catalytic properties re-ected by their remarkable efficiency and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Another physical method which has been used for defect creation in 2D materials is ion implantation. [93][94][95][96][97] Significant research has been devoted to ion implantation, which is frequently applied to modify 2D materials through the creation of vacancies, doping and intercalation. Interestingly, electron/ion bombardment of 2D layered materials creates vacancies as defects.…”
Section: Ion Implantationmentioning
confidence: 99%
“…Doping with foreign atoms such as transition metals allows to add functionality to graphene and to tailor its properties for applications ranging from magnetism and spintronics to single-atom catalysis. However, substitutional incorporation of transition metal atoms in graphene is generally not energetically favorable (smaller binding energy for the impurity than for the C atom) due to a different nature of chemical bonding in graphene and in metallic systems.…”
Section: Introductionmentioning
confidence: 99%